Geflüchtete, Migranten oder Jugendliche mit DaZ? Zwischenergebnisse aus dem Projekt ForEST - Michalak, Magdalena; Winter, Evelina (Spracharbeit mit Geflüchteten - Empirische Studien zum Deutscherwerb von Neuzugewanderten, 2022)
Using data from the ForEst (Formative evaluation of SPRINT (= SPRachförderung INTensiv [intensive language support])) (cf. Michalak/Grimm/Lotter 2018), the authors discuss the wide range of individual learning conditions of lower secondary level students who have recently immigrated, their development over the course of three school years and its significance for shaping language work and for the design of a research project. The focus is particularly on the previous language-related and digital experience of students enrolling in lower secondary level school in Germany from other school systems. Based on persuasive texts written by students (n = 958) from the ForEST corpus, the authors start by analyzing how this heterogeneous target group uses its linguistic potential in German during the early phase of second language acquisition and how this potential is unleashed. The assessments show that a mixed methods approach (cf. Kuckartz 2014) enables resource-oriented access to recording (even minimal) progress of the target group in a nuanced manner and to explaining it to benefit the design of targeted language support. The authors conclude by outlining the consequences for teaching German as a Second Language and for empirical research with students who have recently immigrated, based on the results.<br
Keywords: heterogeneous learning prerequisites; writing skills; newly enrolled lower secondary level students; language education; language development phases